ICT Literacy and Self-Directed Learning through E-Module - Dewi Surani; Januarius Mujiyanto; Rudi Hartono; Zulfa Sakhiya (Universitas Negeri Semarang, 2022)
Information and communication technology (ICT) literacy is crucial for students in order to better prepare them for the digital learning era. It facilitates the development of self-directed learning (SDL). The goal of this study is to describe the implementation of law students’ ICT literacy and self-directed learning (SDL) abilities through E-Module in learning process. A qualitative approach and a descriptive method are used in the study. This study’s primary data were results of the ICT literacy assessment questionnaires, and secondary data were terms of ICT literacy and self-directed learning, and several interviews with law students. The data were collected through open questionnaires that were distributed online via a google form and analyzed through the process of data reduction, data presentation, data collection, and verification. The results of the study note that, the student's knowledge of information and communication technology (ICT) allows them to learn independently using an e-module. Students gain access to the E-Module in order to complete lecture assignments using their knowledge of information and communication technology (ICT). The fact that they are accessing an electronic module reflects their level of self-directed learning (SDL), as well as their literacy and self-directed learning support achievement.